2014
DOI: 10.1128/ec.00220-13
|View full text |Cite
|
Sign up to set email alerts
|

WetA Is Required for Conidiogenesis and Conidium Maturation in the Ascomycete Fungus Fusarium graminearum

Abstract: c Fusarium graminearum, a prominent fungal pathogen that infects major cereal crops, primarily utilizes asexual spores to spread disease. To understand the molecular mechanisms underlying conidiogenesis in F. graminearum, we functionally characterized the F. graminearum ortholog of Aspergillus nidulans wetA, which has been shown to be involved in conidiogenesis and conidium maturation. Deletion of F. graminearum wetA did not alter mycelial growth, sexual development, or virulence, but the wetA deletion mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 90 publications
(130 reference statements)
3
67
0
Order By: Relevance
“…The transcript levels of five genes, STUA 30, HTF1 31, REN1 32, ABAA 33, and WETA 34, were significantly decreased in the HK226 mutant strains compared to the wild-type strain (Fig. 2d).…”
Section: Resultsmentioning
confidence: 95%
“…The transcript levels of five genes, STUA 30, HTF1 31, REN1 32, ABAA 33, and WETA 34, were significantly decreased in the HK226 mutant strains compared to the wild-type strain (Fig. 2d).…”
Section: Resultsmentioning
confidence: 95%
“…As a typical SR protein, FgSrp1 appears to play an important role in regulating pre‐mRNA processing and expression of over 2500 genes in F. graminearum . Among the genes that were significantly down‐regulated in the Fgsrp1 mutant, a number of them are known to be important for vegetative growth, conidiation, sexual reproduction and pathogenesis, including the ZIF1, WETA and ABAA transcription factor genes, PTH11 ortholog (receptor), PPG1 (pheromone precursor), FSR1 (transporter), HMR1 (HMG‐CoA reductase), AXL2, FgERG4 (Seong et al ., ; Shim et al ., ; Wang et al ., ; Si et al ., ; Liu et al ., ; Son et al ., ). Reduced expression of these genes may contribute to the defects of the Fgsrp1 mutant in hyphal growth, asexual and sexual development and plant infection.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a microscopic analysis revealed that F. fujikuroi Wet1 is likely involved in conidia maturation, as already established for the A. nidulans and F. graminearum WetA homologs. Thus, Aspergillus WetA affects the conidial cell wall composition as well as trehalose accumulation (Sewall et al, 1990;Tao and Yu, 2011), while F. graminearum ΔwetA mutants had malformed and longer conidia with fewer septa that were sensitive to stressors (Son et al, 2014b). Although the exact role of F. fujikuroi Wet1 remains to be elucidated, one can deduce a conserved role of this protein in conidia separation and maturation for all three filamentous fungi.…”
Section: Set1 and Kdm5 Regulate The Conidiation-specific Tf Gene Aba1mentioning
confidence: 99%